Catalytic Stereoselective Conjugate Addition of Oxindole to Electron‐Deficient Alkynes. Issue 2 (29th January 2013) - Kang, Guowei; Wu, Quanquan; Liu, Miaochang; Xu, Qingfang; Chen, Zunyang; Chen, Weilong; Luo, Yuqiang; Ye, Wei; Jiang, Jun; Wu, Huayue
Abstract A Z/E‐selective and enantioselective conjugate addition of oxindoles to butyl but‐2‐ynedioate derivatives has been developed, providing a facile access to enantioenriched multifunctional olefins, which can be further converted into 3, 3a‐ dihydro‐2H‐pyrrolo[3, 4‐c]quinoline‐1, 4(5H, 9bH)‐dione derivatives via conventional operations.